288 THE ROLE OF PLASMEPSIN 10 IN OOKINETE EGRESS THROUGH THE MOSQUITO MIDGUT. Issue 1 (1st January 2007) - Bounkeua, V.; Li, F.; Patra, K.; Vinetz, J. M.
Abstract : Background: Successful development of a malaria vaccine would have a global impact. A vaccine to block transmission of Plasmodium to mosquitoes would protect individuals and populations from malaria. While some Plasmodium aspartic proteases (plasmepsins) are known to degrade hemoglobin in the blood stages, proteomic and expression profiling data suggest that other plasmepsins, including PM 10, are present in ookinetes, the mosquito-invasive stage of the parasite. The stage-specific expression of PM 10 implies a novel and yet uncharacterized function for this protease in parasite invasion of the mosquito. We hypothesize that interference of PM 10 will prevent parasite migration through the mosquito midgut wall, thus validating this molecule as a target for blocking malaria transmission. Methods: Three species of Plasmodium were used in this study: P. falciparum, P. berghei, and P. gallinaceum . Anti-PM 10 monoclonal antibodies were used for immunofluorescence and immunoelectron localization of the protein within blood stage parasites and zygote/ookinetes. Experimental mosquito infections were performed in the presence of the mAbs using glass membrane feeders. Results: Localization studies demonstrated apical surface localization of PMX on the parasite, suggesting a role for the enzyme in midgut penetration. The effect of the anti-PMX mAb on transmission is currently under investigation. Discussion: Subcellular localization of plasmepsin X suggests a novel role for a Plasmodium aspartic protease in parasite development and invasion of the mosquito midgut. These results support the hypothesis that ookinete-expressed PM X is a promising target for blocking malaria transmission. Further studies are required to elucidate the precise mechanism by which the ookinete PM X mediates midgut invasion.